Introduction to Special Collection on Arctic Ocean Modeling and Observational Synthesis (FAMOS) 2: Beaufort Gyre Phenomenon. Issue 2 (5th February 2020) - Proshutinsky, A.; Krishfield, R.; Timmermans, M.‐L.
Abstract: One of the foci of the Forum for Artic Modeling and Observational Synthesis (FAMOS) project is improving Arctic regional ice‐ocean models and understanding of physical processes regulating variability of Arctic environmental conditions based on synthesis of observations and model results. The Beaufort Gyre, centered in the Canada Basin of the Arctic Ocean, is an ideal phenomenon and natural laboratory for application of FAMOS modeling capabilities to resolve numerous scientific questions related to the origin and variability of this climatologic freshwater reservoir and flywheel of the Arctic Ocean. The unprecedented volume of data collected in this region is nearly optimal to describe the state and changes in the Beaufort Gyre environmental system at synoptic, seasonal, and interannual time scales. The in situ and remote sensing data characterizing ocean hydrography, sea surface heights, ice drift, concentration and thickness, ocean circulation, and biogeochemistry have been used for model calibration and validation or assimilated for historic reconstructions and establishing initial conditions for numerical predictions. This special collection of studies contributes time series of the Beaufort Gyre data; new methodologies in observing, modeling, and analysis; interpretation of measurements and model output; and discussions and findings that shed light on the mechanisms regulating Beaufort Gyre dynamics as it transitions to a new state under different climate forcing. Key Points: Introduction to the FAMOS‐2 special collection with papers mainly on studies in the region of the Arctic Ocean's Beaufort Gyre Physical, geochemical, biological, and ecosystem components of the Beaufort Gyre system are investigated New observations, ideas, and hypotheses revealing mechanisms influencing the Beaufort Gyre are discussed